Impact of Wage Digitization on the Savings and Financial Inclusion of Tea Garden Workers of West Bengal (India) - Nasim Ansari, Md; Jamaluddeen (Arthshastra Indian Journal of Economics & Research, 2023)
Purpose : This study examined the possible economic and social gains of tea garden laborers in West Bengal because of wage digitalization. The emphasis was on increasing wage transparency, encouraging financial inclusion, and helping tea garden workers manage their money more effectively. Methodology : The study involved 390 laborers from 12 tea estates in North Bengal and used empirical methods to monitor and quantify the impacts of wage digitalization on savings, income management, and financial inclusion. To conclude, the study applied descriptive statistics, paired t-tests, bi-variate regression, and Garret’s ranking technique. Findings : The findings indicated positive impacts of wage digitization on savings increment, control over income, and financial inclusion for tea garden workers of West Bengal. Notably, there was an increase in savings, enhanced income control, and significantly encouraged financial inclusion. Based on the findings, the top three benefits were increased savings, income management, and time-saving. On the other hand, the top three significant obstacles were the distance from bank branches, the unavailability of ATMs, and wage withdrawal charges. Policy Implications : Digitizing tea garden wages will yield vital policy implications that will highlight enhanced savings and financial inclusion. Advocating digital payment policies benefits workers and management, extending to organized, semi-organized, and unorganized sectors, addressing prevalent cash-based wage systems, and benefiting earners and payers. Originality : This study enhanced the literature by empirically exploring wage digitalization’s impact on West Bengal tea estates. Concrete evidence revealed positive effects on workers’ savings, income management, and financial inclusion. The research addressed issues and offered recommendations for successful digitalization implementation in diverse economic and social contexts.